2022
DOI: 10.1108/ajb-10-2021-0136
|View full text |Cite
|
Sign up to set email alerts
|

I am more inclined to buy online–novel social media engagement stimulated purchase intentions post-COVID-19: a case of Pakistani market

Abstract: PurposeThis study sheds light on the differential impact of social media brand engagement on two distinct types of purchase intentions, i.e. online and physical, in the special context of the post-COVID-19 situation in Pakistan. It has shed light on the factor (trust in online purchases during COVID-19) that has shaped the post-pandemic purchasing attitude. The above-stated association is unlocked based on the mediating role of brand equity.Design/methodology/approachThe people who followed the social media pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 71 publications
(153 reference statements)
0
3
0
Order By: Relevance
“…According to Yoo et al (Yoo et al, 2000) 'brand image' is the combination of brand awareness and brand association. In addition to this, the relationship between social media participation and consumers' intentions to make both online and offline purchases is mediated by brand equity (Fatima et al, 2022). The protocol of brand images and brand association has different categories of products (Low, Lamb, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Yoo et al (Yoo et al, 2000) 'brand image' is the combination of brand awareness and brand association. In addition to this, the relationship between social media participation and consumers' intentions to make both online and offline purchases is mediated by brand equity (Fatima et al, 2022). The protocol of brand images and brand association has different categories of products (Low, Lamb, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Consumer's Purchasing Intentions: The emerging usage of the Facebook platform, and advertising is altering the business world, in reaction to the consumer's needs and desires (Imtiaz et al, 2021). Another study shows the factor of trust in online purchases increases during COVID-19, with online buy intentions, whereas, social media participation shows a weaker correlation with physical purchase intentions (Fatima et al, 2022). In social media platforms, credibility and trust are still crucial in attracting the consumer's engagement in online media ( Van et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Further, literature suggests that there exists a cause-and-effect relationship between social media engagement and purchase intentions (Fatima et al, 2022). Park et al (2021) found that a positive relationship exists between engagement with social media pages of brands and consumer behaviors, including purchase intentions.…”
Section: Mediation Of Social Media Engagementmentioning
confidence: 99%
“…A three-item measure for differentiation-oriented content was adapted from the study of Lee and Hong (2016). Social media engagement was investigated by a five-item measure adapted from Fatima et al (2022) and Chahal and Rani (2017). Purchase intentions were investigated by a three-item measure adapted from Fatima et al (2022) and Davidson et al (2019).…”
Section: Operationalization Of Variablesmentioning
confidence: 99%
“…Many businesses are adapting to new technologies and using ecommerce platforms to promote their products (Akram et al, 2022). A customer can decide what to buy at home by looking at and comparing the prices of different competitors' products (Fatima, 2022). The growth and success of a business can be identified by how well its customers are satisfied and how well they remain loyal.…”
Section: Introductionmentioning
confidence: 99%